Konstruksi Teks â€œAtap Rumah Bangsaâ€ Bertajuk â€œLomba Avatar ARBâ€ sebagai Sarana Marketing Politik - Putri, Melisa Indriana (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Political marketing is considered as tool to introduce the party or political leaders effectively to public. Ahead of the 2014 election, some text of certain candidates or political parties were present. Undesirable condition when texts were used as a hidden campaign tool in the gray area on media regulation, especially in television. This study describes how text of â€œAtap Rumah Bangsaâ€ on TV One and ANTV in 2013 is being built. This study uses semiotic analysis of Roland Barthes and the results stated that text of â€œAtap RumahBangsaâ€ through â€œLomba Avatar ARBâ€ constructs positive image of ARB and Golkar.